2011
DOI: 10.1021/cs100069f
|View full text |Cite
|
Sign up to set email alerts
|

Anchored Wilkinson Catalyst

Abstract: A series of Anchored Wilkinson’s Catalysts were prepared by the reaction of the homogeneous Wilkinson catalyst with alumina/heteropoly acid support materials. It was found that the catalytically active species from these materials were unique in that they had only a single triphenylphosphine and a heteropoly acid as ligands giving these catalysts distinctive steric and electronic characteristics. These catalysts were used to promote the hydrogenation of 1-hexene and limonene with substrate to catalyst ratios o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…At low pressure, all catalysts, except Ru, independent of the supports were menthene selective. It was reported that hydrogenation of the limonene's endocyclic double bond was disfavored compared to the exocyclic double bond's hydrogenation [26]. It was also reported that Ru/C has smallest nanoparticles (1.5 nm), compared to the other investigated metals, which could explain its inactivity on our hydrogenation [29].…”
Section: Catalyst Comparisonmentioning
confidence: 74%
See 1 more Smart Citation
“…At low pressure, all catalysts, except Ru, independent of the supports were menthene selective. It was reported that hydrogenation of the limonene's endocyclic double bond was disfavored compared to the exocyclic double bond's hydrogenation [26]. It was also reported that Ru/C has smallest nanoparticles (1.5 nm), compared to the other investigated metals, which could explain its inactivity on our hydrogenation [29].…”
Section: Catalyst Comparisonmentioning
confidence: 74%
“…Partial hydrogenation of limonene to menthene tends to be problematic due to overreduction. Limonene hydrogenation using Wilkinson's catalyst confirmed that the hydrogenation of the endocyclic double bond is disfavored [26]. Following hydrogenation of limonene over Pd/C and Pd/ Alumina catalysts at room temperature and 0.1 MPa of hydrogen pressure, side products, such as terpinolene, g-terpinene, and p-cymene, were formed besides menthene and menthane [27].…”
Section: Introductionmentioning
confidence: 99%
“…functionalized a mesoporous SBA‐15 support with a triphenylphosphine rhodium carbonyl complex and found excellent activity for olefin hydrogenation . A series of alumina/heteropolyacid anchored Wilkinson catalysts have shown to be active towards the reduction of 1‐hexene with 85 % of conversion …”
Section: Introductionmentioning
confidence: 99%
“…[42] As eries of alumina/heteropolyacid anchored Wilkinson catalysts have shown to be active towards the re-ductionof1 -hexene with 85 %o fc onversion. [43] Herein, we describe the formation of rhodium(I)-modified NDs (NDs-Rh) using asurface-immobilized catechol phosphane ligand (1). While the catechol part provides immobilizationo f the ligand via interaction with the hydroxyl groups of oxidized NDs, [14,17] the phosphane functions will coordinate to transition metal centers and form surface-bound molecular complexes.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature, it is known that Pd based catalysts are widely used for acetoxylation reactions [3][4][5][6] in general and toluene acetoxylation in particular [5,7,8]. Most of the work reported so far was carried out under liquid-phase conditions and in batch reactors [5,9].…”
Section: Introductionmentioning
confidence: 99%